Pengaruh Strategi Pemasaran terhadap Minat Beli dengan Inovasi Produk sebagai Variabel Intervening pada Generasi Z : Studi Kasus pada Mahasiswa Prodi Manajemen Universitas Negeri Makassar - Aswar, Nurul Fadilah (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This research examines the impact of marketing strategies on purchase intention, with product innovation serving as an intervening variable among Generation Z. Focusing on students in the Management program at Universitas Negeri Makassar, the research highlights how technology advancements and changing consumer behavior require businesses to adopt more innovative marketing strategies. The study explores how product innovation, influenced by marketing efforts, plays a critical role in shaping the purchase decisions of these younger generations. Using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method, the study reveals that while marketing strategies directly affect purchase intention, product innovation further enhances the appeal of products to Generation Z consumers. The findings provide insights for businesses to effectively design marketing strategies that align with the dynamic preferences of these generations, ultimately driving consumer loyalty and competitiveness in a rapidly evolving market.